Studi Deskriptif Kompetensi Pedagogik Guru dalam Pembelajaran Musik Ensambel Sejenis di Madrasah Tsanawiyah Negeri 1 Kerinci - Afdhal Syukron; Jagar Lumbantoruan (FBS Universitas Negeri Padang, 2022)
Learning similar musical ensembles is one of the learning materials in arts and culture subjects at Madrasah Tsanawiyah Negeri (MTsN) 1 Kerinci. The formulation of the problem in this study is to describe the pedagogical competence of teachers who teach arts and culture, include: (1) Understanding the characteristics of students, namely understanding the physical, intellectual, social, emotional, moral and socio-cultural backgrounds. (2) Mastering learning theory, namely adjusting the learning method according to the subject matter. (3) Developing a curriculum, namely making, selecting, compiling, and developing the right curriculum for students. (4) Organizing educational learning activities, namely increasing student competence in observing listening, seeing, reading, listening, asking questions, associations, concluding, and communicating. (5) Utilizing technology in learning. (6) The development of the potential of students, namely providing facilities for the realization of the potential development of students. (7) Communication with students, namely creating interaction with students. (8) Conduct assessment and evaluation, (9) Conduct reflective activities in similar musical ensemble learning at MTsN 1 Kerinci.